2020
DOI: 10.5483/bmbrep.2020.53.4.220
|View full text |Cite
|
Sign up to set email alerts
|

Dehydrocostus lactone inhibits NFATc1 via regulation of IKK, JNK, and Nrf2, thereby attenuating osteoclastogenesis

Abstract: Excessive and hyperactive osteoclast activity causes bone diseases such as osteoporosis and periodontitis. Thus, the regulation of osteoclast differentiation has clinical implications. We recently reported that dehydrocostus lactone (DL) inhibits osteoclast differentiation by regulating a nuclear factor of activated T-cells, cytoplasmic 1 (NFATc1), but the underlying mechanism remains to be elucidated. Here we demonstrated that DL inhibits NFATc1 by regulating nuclear factor-B (NF-B), activator protein-1 (AP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…AMPK and Nrf2 were also reported to be involved in Gram-positive bacteria-mediated inflammation [ 41 ], and activation of the AMPK/Nrf2 signaling pathway could reduce inflammation by enhancing M2 polarization [ 13 ]. A previous study found that DHL exhibits the ability to activate Nrf2 [ 42 ]; our results make this finding more credible, as DHL promotes the phosphorylation of AMPK, an upstream gene of Nrf2, as well as accelerates the expression and nuclear translocation of Nrf2. HO-1, a downstream gene of Nrf2, has also been demonstrated to alleviate inflammation by altering the balance of M1/M2 macrophages [ 14 , 43 ].…”
Section: Discussionsupporting
confidence: 69%
“…AMPK and Nrf2 were also reported to be involved in Gram-positive bacteria-mediated inflammation [ 41 ], and activation of the AMPK/Nrf2 signaling pathway could reduce inflammation by enhancing M2 polarization [ 13 ]. A previous study found that DHL exhibits the ability to activate Nrf2 [ 42 ]; our results make this finding more credible, as DHL promotes the phosphorylation of AMPK, an upstream gene of Nrf2, as well as accelerates the expression and nuclear translocation of Nrf2. HO-1, a downstream gene of Nrf2, has also been demonstrated to alleviate inflammation by altering the balance of M1/M2 macrophages [ 14 , 43 ].…”
Section: Discussionsupporting
confidence: 69%
“…Bone marrow‐derived macrophages (BMMs) were prepared as osteoclast precursor cells as previously described (Lee et al, 2020). Bone marrow cells were flushed from femurs and tibiae of 8‐week‐old C57BL/6 male mice using α‐minimum essential medium (α‐MEM) containing 10% fetal bovine serum (FBS), 100 U/ml penicillin, and 100 μg/ml streptomycin followed by incubation at 37°C for 1 day.…”
Section: Methodsmentioning
confidence: 99%
“…Bone marrow-derived macrophages (BMMs) were prepared as osteoclast precursor cells as previously described (Lee et al, 2020).…”
Section: Preparation Of Bone Marrow-derived Macrophagesmentioning
confidence: 99%
“…These data suggested that NRF2 is crucial to OC activity, but the underlying mechanism of NRF2 in regulating OC activity remains unclear [123]. Increased p38 MAP kinase activity but not the NF-kB pathway was associated to ROS elevation in NFR2 knockout mice [124][125][126][127]. Moreover, NRF2 also represses OC activity via regulating the activity of NFATc1, which is the master transcription factor for osteoclastogenesis [124,128].…”
Section: The Effects Of Nrf2 On Ocmentioning
confidence: 99%